K2CO3 in NH4OH as an Effective Catalyst Mixture for the Transesterification of High Acid Value Mahua Oil - Swarna, S.; Swamy, M.T.; Divakara, T.R.; Krishnamurthy, K.N.; Shashidhar, S.; Srikanth, H.V. (Asian Journal of Chemistry, 2021)
In present study, biodiesel was synthesized from high free fatty acid content Mahua oil using K2CO3 in NH4OH catalyst mixture through transesterification process. Addition of NH4OH to K2CO3, enhanced the basic strength of the catalyst (K2CO3) by generating in-situ KOH in ammonium carbonate medium. The presence of ammonium carbonate in the reaction medium controlled the generation of intermediate water during methoxide formation and thereby increased the biodiesel yield. The maximum yield of 98.5% with a fatty acid methyl ester (FAME) content of 98.95% was obtained at the optimized condition of catalyst mixture of 1g K2CO3 in 0.5 g of NH4OH, oil to methanol molar ratio 1:7 at 55 ºC in 75 min. Characterization of the obtained biodiesel has been carried out using GC-MS and 1H NMR techniques. The physico-chemical properties of the oil and the synthesized biodiesel were tested according to the ASTM D6751 standards and the values are within the range.